Cancer-Associated Fibroblasts and Tumor-Associated Macrophages in Cancer and Cancer Immunotherapy - Raskov, Hans; Orhan, Adile; Gaggar, Shruti; Gögenur, Ismail (Frontiers in Oncology, 2021)
Our understanding of the tumor microenvironment (TME), including the interplay between tumor cells, stromal cells, immune cells, and extracellular matrix components, is mandatory for the innovation of new therapeutic approaches in cancer. The cell-cell communication within the TME plays a pivotal role in the evolution and progression of cancer. Cancer-associated fibroblasts (CAF) and tumor-associated macrophages (TAM) are major cell populations in the stroma of all solid tumors and often exert protumorigenic functions; however, the origin and precise functions of CAF and TAM are still incompletely understood. CAF and TAM hold significant potential as therapeutic targets to improve outcomes in oncology when combined with existing therapies. The regulation of CAF/TAM communication and/or their differentiation could be of high impact for improving the future targeted treatment strategies. Nevertheless, there is much scope for research and innovation in this field with regards to the development of novel drugs. In this review, we elaborate on the current knowledge on CAF and TAM in cancer and cancer immunotherapy. Additionally, by focusing on their heterogenous functions in different stages and types of cancer, we explore their role as potential therapeutic targets and highlight certain aspects of their functions that need further research.